Monetary policy, asset prices and macroeconomic conditions: a panel-VAR study - Katrin Assenmacher-Wesche; Stefan Gerlach (National Bank of Belgium, 2008)
This paper studies the relationships between inflation, economic activity, credit, monetary policy, and residential property and equity prices in 17 OECD countries, using quarterly data for 1986-2006. Using a panel VAR, we find plausible and significant responses to a monetary policy shock. Shocks to asset prices have a positive, significant effect on GDP and credit after three to four quarters, whereas prices start to increase much later. We also consider the transmission of US shocks from the US to the other economies. While monetary policy shocks are transmitted internationally, other shocks are not, perhaps because of the form of coefficient restrictions used.
Keywords: C23; E52; 330; asset prices; credit; monetary policy; panel VAR; Geldpolitik; Immobilienpreis; Schock; Kreditmarkt; Geldpolitische Transmission; OECD-Staaten